Karakteristik Karbon Aktif Tempurung Kluwak (Pangium edule) Sebagai Adsorben Pada Penjerapan Methylene Blue - Andi Musfirah Adhar; Isma Ayu Ningsih Putri Zainal; Farham; Ida Adriani Idris; Haera Setiawati; Yuliani HR (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Kluwak (Pangium edule) is a plant that the seeds are used as a seasoning, to produce waste in the form of kluwak shells that the application has not been widely used by the community. This study aims to utilize the carbonized kluwak shell waste as an adsorbent for the absorption of methylene blue, by activating them using potassium hydroxide (KOH) to increase the adsorption ability of the adsorbent. Variations in the concentrations of KOH used are 0, 1, 3, and 5 M and concentrations of methylene blue solution 100, 110, 120, 130, 140, and 150 ppm. The study reviewed how the characteristics of the kluwak shell as an adsorbent on the absorption of methylene blue, including absorption percentage, maximum adsorption capacity through Langmuir equation, adsorbent morphology through Scanning Electron Microscope (SEM) analysis, and surface area. The adsorption process in this study took place in batches for 90 minutes using a shaker with speed of 300 rpm with volume methylene blue solution as much as 50 mL and the weight of the kluwak shell carbon without activation, and KOH 1, 3, and 5 M activated kluwak shell carbon as much as 0.15 g. The results showed that the higher the concentration of KOH, the higher the average adsorption percentage and maximum adsorption capacity. The amount of the average percent absorption, maximum adsorption capacity, and the largest surface area were on the kluwak shell carbon activated by KOH 5 M, were respectively 97.69%; 48.082mg/g; and 174.17 m2/g. The SEM results analysis showed that activated kluwak shell carbon of 5 M KOH had a larger particle size and pore shape, had a more unified shape, and a flake structure than without activation.